Peri-Vesical Fat Interposition Flap Reinforcement in High Vesico-Vaginal Fistulas - Singh, R. B. (Medknow Publications, 2010)
BACKGROUND AND AIM: The urinary bladder becomes small, contracted and is associated with excess pelvic fat in long standing cases of vesico-vaginal fistulas (VVFs). The aim of this new technique was to use this excess pelvic fat for harvesting an interposition flap. MATERIALS AND METHODS: An interposition flap of peri-vesical fat was raised from the anterior, superior and posterior surfaces of the urinary bladder and was interposed between the right angle closed vaginal vault and the urinary bladder to strengthen the repair. This technique was used in two patients of VVFs. RESULTS: Both the patients had successful outcome and were able to retain sufficient quantity of urine at 3 months follow-up. CONCLUSIONS: Peri-vesical fat flap proved an effective interposition flap in the repairs of VVFs in selected cases.